The antitumor mechanisms of glabridin and drug delivery strategies for enhancing its bioavailability - Li, Chong; Wang, Yu; Zhang, Wenjing; Yang, Xiaoman; Wang, Yufang; Hou, Guanqun; Wang, Dongli; Han, Bingbing; Zhang, Yimin (Frontiers in Oncology, 2024)
Glabridin, a flavonoid derived from the plant Glycyrrhiza glabra, has garnered significant attention due to its diverse pharmacological effects, including antioxidant, antibacterial, anti-inflammatory, hypolipidemic, and hypoglycemic activities. Studies have shown that glabridin exhibits substantial antitumor activity by modulating the proliferation, apoptosis, metastasis, and invasion of cancer cells through the targeting of various signaling pathways, thus indicating its potential as a therapeutic agent for malignant tumors. To enhance its solubility, stability, and bioavailability, several drug delivery systems have been developed, including liposomes, cyclodextrin inclusion complexes, nanoparticles, and polymeric micelles. These de.livery systems have shown promise in preclinical studies but face challenges in clinical translation, such as issues with biocompatibility, delivery efficiency, and long-term stability. A comprehensive analysis of the antitumor mechanism of glabridin and its novel drug delivery system is still lacking. Therefore, the authors performed a comprehensive review of recent literature on the antitumor effects of glabridin and its novel drug delivery systems, covering the antitumor mechanism, action targets, and novel drug delivery systems, offering new theoretical insights and development directions for its further advancement and clinical application.